ATAM-RPG: A role-playing game to teach architecture trade-off analysis method (ATAM) (2017)
Teaching software architecture to undergraduate students is particularly hard because they typically have no experience with medium or large systems with competing stakeholders. A particularly hard case is ATAM (Architecture Trade-off Analysis Method), which allows the evaluation of architectural designs and quality attributes by competing stakeholders. This article describes ATAM-RPG, a role-playing game to support the teaching of ATAM by simulating stakeholder's interaction and trade-offs. The initial ATAM-RPG case incorporates the architecture, scenarios and design trade-offs of the Chilean national tsunami alert system (SNAM). The approach was tested by deploying the SNAM case in undergraduate courses; initial results show that ATAM-RPG was well-evaluated regarding trade-off description and understanding (and especially utility trees). Students also recognized the importance of exercising technically-based negotiation skills. We conclude that role playing games can be fruitfully used for software architecture education. © 2017 IEEE.